USE OF WOOD GREENING OF CONIFEROUS BREEDS BRIEF REVIEW OF PATENTS - Shegelman I. R., Vasilyev A. S., Kirilina V. M. (Relevant lines of scientific research: theory and practice, 2019)
considered patents aimed at developing new intellectual property in the field of technologies and equipment for the use of coniferous wood greens.
Keywords: интеллектуальная собственность; патент; intellectual property; база знаний; knowledge base; patent; древесная зелень; недревесные ресурсы леса; non-timber forest resources; хвойные породы; conifers; green wood